Analisis Nilai Tambah Pengolahan Kelapa Menjadi Virgin Coconut Oil di Kabupaten Nias Selatan, Provinsi Sumatera Utara - Pereira, Diego Mendes; Ambarawati, I Gusti Agung Ayu; Budiasa, I Wayan (JURNAL MANAJEMEN AGRIBISNIS (Journal Of Agribusiness Management); Vol 8 No 1 (2020): MEI 2020DO - 10.24843/JMA.2020.v08.i01.p02, 2020)
As a country that has the largest coconut plantations in the world, Indonesia has the potential and opportunity to become a world leader in the production of processed coconut. South Nias Regency has good potential in coconut processing, but has not been utilized optimally. The only coconut processing company producing Virgin Coconut Oil (VCO) in South Nias Regency is CV Ononiha Oil, and this company provides guidance to the surrounding coconut farmers. The purpose of this study is to determine the added value, labor benefits, and profit of processing coconut into VCO, and to analyze the production and marketing constraints of VCO in South Nias Regency. This research was conducted in South Nias Regency, North Sumatra Province, with coconut processing farmers into VCO and the company CV Ononiha Oil. The determination of key respondents was carried out through purposive sampling, namely the owner of the CV Ononiha Oil and ten respondent farmers were chosen using the census method. Value added analysis in this study uses the Hayami method. The results showed that the added value, labor benefits, and the highest profits were at the farm level, where farmers get added value of Rp 9.522 while the company gets an added value of Rp 4.833 in one production process cycle; farmers' labor compensation is Rp 3.389, compared to the company only Rp 960; profit at the farmer level is Rp 6.132, while at the company is Rp 3.873. The obstacles faced by farmers are the limited absorption of the local market and the lack of permission from PIRT (Pangan Industri Rumah Tangga – Home Industry Food) to enter larger markets such as supermarkets or markets outside the district. The constraints that exist on both the farmer and the company CV Ononiha Oil are on the management and marketing side which is less efficient, and has not yet obtained an organic certificate. Farmers and companies are expected to be able to enter the broader market by certifying their products and improving management capabilities.